Breakfast with Neruda - Moe, Laura (Merit Press/FW, 2016)
Leaving his chaotic home to live in a 1982 station wagon, teenaged Michael is performing mandatory community service when he meets Shelly, girl with a past, who may be special enough to unmask Michael's deepest secrets and reveal his immense heart.